digitization as a modern strategie mechanisme in the organisational development of the youth and sports sector in souk ahras - قنادزية عبد الغاني (My University, 2024)
الملخص : تهدف هذه الدراسة الى التعرف على "دمج الرقمنة كآلية استراتيجية حديثة في التطوير التنظيمي "الشبابوالرياضة لولاية سوق اهراس، والتعرف على نوع العلاقة بين دمج الرقمنة وابعاد التطوير التنظيمي (الأفراد، جماعات العمل، التنظيم نفسه) واستخدمنا المنهج الوصفي التحليلي مع أداة البحث والاستمارة، الاستبيان في بحثنا وتمثلت عينة دراستنا في 66 موظف اداري من مديرية الشباب والرياضة وديوان مركب متعدد الرياضات لولاية سوق اهراس واخترنا العينة بطريقة المسح الشامل ومن اهم النتائج المتوصل اليها: - انه توجد درجة مرتفعة لدمج الرقمنة كآلية استراتيجية حديثة في قطاع الشباب والرياضة - كما توجد درجة متوسطة لبعد الافراد للتطوير التنظيمي في المؤسسات الرياضية، وتوجد درجة متوسطة لبعد جماعات العمل للتطوير التنظيمي في المؤسسات الرياضية، كما توجد درجة متوسطة لبعد التنظيم نفسه للتطوير التنظيمي في المؤسسات الرياضية وتوصلنا الى وجود علاقة ارتباطية موجبة قوية بين محور الرقمنة كآلية استراتيجية وابعاد التطوير التنظيمي للمؤسسات الرياضية لولاية سوق أهراس. abstract : This study aims to identify "the integration of digitization as a modern strategic mechanism in organizational development «in the youth and sports directorate at the state of Souk Ahras. As well as, to identify the type of relationship between the integration of digitization and the dimensions of organizational development (individuals, work groups, the organization itself). We used the analytical descriptive method with the research tool and the questionnaire in our research and the sample of our study was 66 administrative staff from the Directorate of Youth and Sports and the Office of a Multi-sports Complex of the state of Souk Ahras. We selected the sample by a comprehensive survey method and the most important findings are: - There is a high degree of integration of digitization as a modern strategic mechanism in the youth and sports sector - There is a moderate degree of the dimension of individuals for organizational development in sports institutions, a moderate degree of the dimension of work groups for organizational development in sports institutions, and a moderate degree of the dimension of the organization itself for organizational development in sports institutions, and a moderate degree of the dimension of the organization itself for organizational development in sports institutions. We found that there is a strong positive correlation between the axis of digitization as a strategic mechanism and the dimensions of organizational development of sports institutions in the state of Souk Ahras. résumé : Cette étude vise à identifier « l'intégration de la numérisation comme mécanisme stratégique moderne dans le développement organisationnel » dans la direction de la jeunesse et des sports de l'état de Souk Ahras. Ainsi que, d'identifier le type de relation entre l'intégration de la numérisation et les dimensions du développement organisationnel (individus, groupes de travail, l'organisation elle-même). Nous avons utilisé la méthode analytique descriptive avec l'outil de recherche et le questionnaire dans notre recherche et l'échantillon de notre étude était de 66 agents administratifs de la direction de la jeunesse et des sports et du bureau d'un complexe multisport de l'état de Souk Ahras. Nous avons sélectionné l'échantillon par une méthode d'enquête exhaustive et les résultats les plus importants sont les suivants : - Il existe un degré élevé d'intégration de la numérisation en tant que mécanisme stratégique moderne dans le secteur de la jeunesse et des sports - Il existe un degré modéré de la dimension des individus pour le développement organisationnel dans les institutions sportives, un degré modéré de la dimension des groupes de travail pour le développement organisationnel dans les institutions sportives et un degré modéré de la dimension de l'organisation elle-même pour le développement organisationnel dans les institutions sportives et un degré modéré de la dimension de l'organisation elle-même pour le développement organisationnel dans les institutions sportives. Nous avons constaté qu’il existe une forte corrélation positive entre l’axe de numérisation en tant que mécanisme stratégique et les dimensions du développement organisationnel des institutions sportives dans l’État de Souk Ahras.
Keywords: الرقمنة; استراتيجية; التطوير التنظيمي; مديرية الشباب والرياضة; ديوان مركب متعدد الرياضات.; Digitization; organizational development; the youth and sports directorate; organizational development of sports institutions.; La numérisation; le développement organisationnel; la direction de la jeunesse et des sports; le développement organisationnel des institutions sportives